Photosensitizer conjugated gold nanorods for photoacoustic imaging - Chee, Medaleine Jee Iue (2014)
Theranostic probes play an important role on the bioimaging and sensing platform to provide diagnostics and therapeutics application. The development of theranostic agent can combine both diagnostics and therapeutics that aids in the process of Photodynamic Therapy (PDT) by allowing the imaging of the disease model. This water soluble photosensitizer that has been frequently used in photothermal therapy, is conjugated with gold nanorods to form a theranostic agent. The known properties of this photosensitizer producing reactive oxygen species (ROS) upon appropriate light irradiation is the key component of PDT that aids in the destruction of cancerous cells.